Aquatic animals and their associates from the Middle Stone Age levels at Sibudu - Plug, I. (Southern African Humanities, 2021)
The Middle Stone Age deposits at Sibudu Cave contain a range of aquatic fauna, much of it accumulated by humans. Other accumulating agents possibly include otters, the marsh mongoose and birds. The marine shell samples are small, but represent a variety of species. Most of the gastropod species present live subtidally, but were collected as washed-up specimens. Their shells are beach worn and do not represent food waste, while others were too small to contribute to the diet. Sibudu is at present about 15 km from the coast, and would have been farther inland during the last Glacial. The representation of marine animals in the deposits suggests regular visits to the coast, but the absence of some prime food mollusc species indicates that any consumption of shellfish took place at the seashore. Their presence in the deposits must therefore have had some other additional function or meaning. To cite this paper: Plug, I. 2006. Aquatic animals and their associates from the Middle Stone Age levels at Sibudu. Southern African Humanities 18 (1): 289-99.